Technical evaluation of the effectiveness of curing products as an option to wet curing of concrete - Rojas, Einer Rodríguez (2022)
This research aims to determine the effects of the use of curing products in hydraulic concrete through laboratory conditions. Although research and technical specifications of curing products indicate improvements in concrete curing, their use and possible advantages must be experimentally verified for the conditions and types of concrete manufactured in Costa Rica. Three types of curing products are used, the first corresponds to a transparent silicate-based curing product that does not produce membrane (C1), the second is a resin-based membrane-forming curing product (C2) and the third is a product Colloidal solution based film-forming curing agent (C3). Through laboratory tests, the compressive strength, modulus of rupture and change in length (expansion or contraction) of concrete are determined for different curing conditions. In general, the results indicate that curing products, at any age of application, do not reduce the expansion or contraction of concrete. For curatives to be adequately effective in developing resistance to shrinkage and flexure in concrete, it must be cured with water for a minimum of three days prior to application of the product. The results suggest better results when applying the curing product 7 days after keeping the specimens in the wet room.